1965
DOI: 10.1103/physrev.137.b752
|View full text |Cite
|
Sign up to set email alerts
|

Wave Functions of Nonlocal Potentials: The Perey Effect

Abstract: An eigenfunction of an attractive nonlocal single-particle potential is always smaller inside the region of the potential than outside; the converse occurs for repulsive potentials. This is the Perey effect. In the present article explicit formulas for the effect are derived for the case of motion in one dimension, and interpretive discussions of the effect are given. The derivation does not employ series expansions. It is argued that the effect can be understood in terms of the fundamental many-body theory fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(40 citation statements)
references
References 12 publications
7
33
0
Order By: Relevance
“…All calculations in [16] were based on the Perey-Buck (PB) optical potential and compared with local-phaseequivalents obtained for this interaction. Consistent with what had been found before [17,18], we found that nonlocality affects the scattering wave functions in the nuclear interior out to the surface region. Non-locality similarly affects the bound state in the nuclear interior, but also beyond the surface region because it changes the asymptotic normalization coefficient.…”
Section: Introductionsupporting
confidence: 81%
“…All calculations in [16] were based on the Perey-Buck (PB) optical potential and compared with local-phaseequivalents obtained for this interaction. Consistent with what had been found before [17,18], we found that nonlocality affects the scattering wave functions in the nuclear interior out to the surface region. Non-locality similarly affects the bound state in the nuclear interior, but also beyond the surface region because it changes the asymptotic normalization coefficient.…”
Section: Introductionsupporting
confidence: 81%
“…If such effects are found to be a common consequence of dynamically generated nonlocality, this is likely to be significant for spectroscopic analyses involving direct reactions. Another suggestive phenomenon revealed by these calculations is the occurrence of an emissive region in the "shadow" edge of the nucleus, a clear indication of flux being returned to the elastic channel, a feature identified by Austern [32] as characteristic of nonlocality.…”
Section: Existing Indications Of Significant Dynamic Nonlocalitymentioning
confidence: 98%
“…For both these latter cases and for 40 Ca, the real-central DPP cannot be represented as a uniform renormalization of the bare potential since the real DPP tends to peak at the nuclear center in this case. This radial shape for the real-central DPP results in an increase of the rms radius of the total potential, whereas, for scattering from the halo nuclei 6 He [3] and 8 He [2,4], the shape of the repulsive DPP is such to decrease the rms radius. This difference currently remains a challenge to the understanding.…”
Section: A Summary Of Findingsmentioning
confidence: 99%
“…Its effects on direct reactions can therefore not be assumed to be accounted for by the usual Perey [7] correction (see also Refs. [8,9]). Moreover, the L dependence is not related to the parity dependence that follows from certain other exchange processes.…”
Section: Introductionmentioning
confidence: 99%